Pengaruh Air gap terhadap Unjuk Kerja Motor Brushless Direct Current 3 Fasa Fluks Aksial Stator Ganda - Hidayah, Bella Octavia Nurul; Hadi, Widyono; Cahyadi, Widya (Majalah Ilmiah Teknologi Elektro, 2020)
Between the stator and rotor there is a gap called the air gap (air gap). In BLDC motors, air gaps can affect motor speed and motor torque. The purpose of this study is to determine the effect of the air gap on the speed and torque produced by the BLDC 3 phase double stator axial flux motor. Tests are carried out at 4 mm and 5 mm air gap, when the motor is not overloaded and when the motor is loaded, at a source voltage of 12V - 15V. The results of testing on the motor are not burdened, ie when the source voltage is increased, the voltage, current, frequency, speed, motor power and torque increase. At a 5 mm water gap, the results of the voltage, frequency and speed have a greater value than the 4 mm water gap. While the results of the motor current, motor power and torque have a smaller value than the 4 mm air gap. The results of the motorized test are when the load and source voltage are increased, the motor voltage, frequency and speed increase. While the current, power and torque of the motor decreases. At the 4 mm water gap, the results of the voltage, frequency and speed of the motor have a greater value than the 5 mm water gap. While the current, power and torque of the motor have a smaller value than the 5 mm air gap.